The new additive to improve the stability of hydrocarbon fuels - Чугуй, В.О.; Іванощук, Т.О.; Шкільнюк, І.О. (Proceedings of National Aviation University (archive), 2009)
The antimicrobial PGMG is offered as biocyde additive for defence of aviation fuels from microbial contamination. The bactericidal concentrations of PGMG are set up for some bacteria separate from a contamination fuel. Influencing of bringing of different concentrations of PGMG in different solvents on the high-quality indexes of fuel is studied.